Matched cohort study of therapeutic strategies to prevent preschool wheezing/asthma attacks - Grigg,J; Nibber,A; Paton,JY; Chisholm,A; Guilbert,TW; Kaplan,A; Turner,S; Roche,N; Hillyer,E; Price,DB; Collaborators,from REG Small Airways Working Group and Child Health Working Group includes; van,Aalderen WMC; et al. (Journal of Asthma and Allergy, 2018)
Background: An inhaled corticosteroid (ICS) or leukotriene receptor antagonist (LTRA) may prevent wheezing/asthma attacks in preschoolers with recurrent wheeze when added to short-acting β-agonist (SABA).Objective: The aim of this historical matched cohort study was to assess the effectiveness of these treatments for preventing wheezing/asthma attacks.Methods: Electronic medical records from the Optimum Patient Care Research Database were used to characterize a UK preschool population (1–5 years old) with two or more episodes of wheezing during 1 baseline year before first prescription (index date) of ICS or LTRA, or repeat prescription of SABA. Children initiating ICS or LTRA on the index date were matched 1:4 to those prescribed only SABA for age, sex, year of index prescription, mean baseline SABA dose, baseline attacks, baseline antibiotic prescriptions, and eczema diagnosis. Wheezing/asthma attacks (defined as asthma-related emergency attendance, hospital admission, or acute oral corticosteroid prescription) during 1 outcome year were compared using conditional logistic regression.Results: Matched ICS and SABA cohorts included 990 and 3,960 children, respectively (61% male; mean [SD] age 3.2 [1.3] years), and matched LTRA and SABA cohorts included 259 and 1,036 children, respectively (65% male; mean [SD] age 2.6 [1.2] years). We observed no significant difference between matched cohorts in the odds of a wheezing/asthma attack: ICS vs SABA, OR (95% CI) 1.01 (0.85–1.19) and LTRA vs SABA, OR (95% CI) 1.28 (0.96–1.72).Conclusion: We found no evidence that initiation of ICS or LTRA therapy is associated with fewer attacks during 1 outcome year than SABA alone for a heterogeneous group of preschool children with recurrent wheeze in the real-life clinical setting.